Differential fibril morphologies and thermostability determine functional roles of Staphylococcus aureus PSMα1 and PSMα3 - Rayan, Bader; Barnea, Eilon; Khokhlov, Alexander; Upcher, Alexander; Landau, Meytal (Frontiers in Molecular Biosciences, 2023)
Phenol-soluble modulins (PSMs) are virulent peptides secreted by staphylococci that undergo self-assembly into amyloid fibrils. This study focuses on Staphylococcus aureus PSMα1 and PSMα3, which share homologous sequences but exhibit distinct amyloid fibril structures. Upon subjecting PSMα1 to an 80°C heat shock, it fibrillates into cross-β structures, resulting in the loss of cytotoxic activity. Conversely, PSMα3 cross-α fibrils undergo reversible disaggregation upon heat shock, leading to the recovery of cytotoxicity. The differential thermostability probably arises from the presence of hydrogen bonds along the β-strands within the β-sheets of the cross-β fibrils. We propose that the breakdown of PSMα3 fibrils into soluble species, potentially co-aggregating with membrane lipids, is crucial for its toxic process and enables the reversible modulation of its biological activity under stress conditions. In contrast, the formation of robust and irreversible cross-β fibrils by PSMα1 corresponds to its role in biofilm stability. These findings emphasize how the unique fibril morphologies and thermostability of PSMα1 and PSMα3 shape their functional roles in various environments of S. aureus.